49. CLINICAL AND PARACLINICAL CHARACTERISTICS OF CHILDREN WITH PNEUMONIA AND A HISTORY OF COVID-19 AT THE PEDIATRICS CENTER OF BACH MAI HOSPITAL. (Vietnam Journal of Community Medicine, 2025)
Objective: To describe characteristics of clinical and paraclinical of children with pneumonia and a history of COVID-19 at the Pediatric Center, Bach Mai Hospital from 2021 to 2022.Subjects and methods: Retrospective descriptive study on 170 pediatric patients at the Pediatric Center, Bach Mai Hospital, including 85 pediatric patients with pneumonia with a history of COVID-19 and 85 pediatric patients with pneumonia without a history of COVID-19 from January 2021 to December 2022.Results: There were 85 children with pneumonia and a history of COVID-19, the average age was 4.11 ± 3.8 years. Among them, the most common clinical symptoms were cough (90.6%), shortness of breath (77.6%), and wheezing (72.9%). Pulmonary rales were the most frequent physical examination finding with 82.4%. The proportion of children with pneumonia exhibiting elevated with white blood cell counts and increase CRP levels was 71.8% and 10.6%, respectively. Chest X-ray findings showed pulmonary lesions in 97.6% patients. Symptoms such as fever, wheezing, and shortness of breath were significantly more frequent in the group of pneumonia patients with a history of COVID-19 compared to those without such a history (p < 0.05). Symptoms of upper respiratory tract inflammation were less common in the COVID-19 history group than in the control group (p < 0.05). Pulmonary rales were also less prevalent in the pneumonia group with a history of COVID-19 compared to the control group (p < 0.05). The group with pneumonia and a history of COVID-19 had an average treatment time of 7.73 ± 4.7 days, with 9.4% of patients staying in hospital for more than 2 weeks. Treatment results showed that 98.8% of patients recovered, while only 1.2% were transferred to the provincial hospital for further treatment.Conclusions: Post-COVID-19 pneumonia has garnered significant attention following the pandemic; however, no clear differences in clinical and paraclinical characteristics have been observed between pneumonia patients with or without a history of COVID-19. Overall, the treatment success rate is high, hospital stays are short, and conventional antibiotic regimens are effective.
Keywords: Pneumonia; COVID-19; children